Computed tomography-guided bronchoalveolar lavage in idiopathic pulmonary fibrosis. Issue 8 (August 1996) - Agusti, C.; Xaubet, A.; Luburich, P.; Ayuso, M. C.; Roca, J.; Rodriguez-Roisin, R.
Abstract : BACKGROUND: High resolution computed tomography (HRCT) is now recognised as a sensitive tool for predicting the histological characteristics of the lung parenchymal abnormalities in patients with idiopathic pulmonary fibrosis (IPF). A reticular pattern on HRCT scanning is indicative of fibrotic histology while a ground glass pattern has been associated with inflammatory disease. The purpose of the present study was to investigate whether the cell population in the bronchoalveolar lavage (BAL) fluid from different lobes differs according to HRCT characteristics in patients with IPF. METHODS: Twenty six patients with IPF (18 men) of mean (SE) age 67 (2) years were included in the study. A semiquantitative analysis of the extent of the abnormalities on the HRCT scan was applied by summing the proportion of both reticular and ground glass patterns in each lobe (expressed as percentage of total area evaluated) and 100 ml double BAL was then randomly performed in the lobe with the most extensive involvement (lobe A) and that with the least extensive involvement (lobe B). RESULTS: Twenty three of the 26 patients (88%) had an abnormal cell count in the BAL fluid from lobe A compared with 18 patients (69%) with abnormalities in the BAL fluid from lobe B. The median (range) percentage of 8.5% (0-34%) and the absolute numbers of neutrophils (1.3 x 10(4)/ml, 0-14.6 x 10(4)/ml) in lobe A were significantly higher than those in lobe B (5% (0-26%) and 1.2 x 10(4)/ml (0-5 x 10(4)/ml), respectively). The percentage (3%, 0-19%) and absolute numbers (0.65 x 10(4)/ml, 0-4 x 10(4)/ml (0-4.8 x 10(4)/ml), respectively). For the group as a whole a correlation was found between the percentage and absolute numbers of neutrophils in the BAL fluid and the total score of abnormalities on the HRCT scan in the most involved lobe (lobe A). Multiple regression analysis indicated that both the percentage and absolute numbers of neutrophils were significantly and independently related to the extent of ground glass pattern. CONCLUSIONS: In patients with IPF the cell population in the BAL fluid is not homogeneous and seems to be related to the characteristics of the abnormalities on the HRCT scan present in the lavaged lobe.